IDENTIFIKASI KEBUTUHAN RUANG DALAM PADA GEDUNG JURUSAN DI POLITEKNIK NEGERI AMBON - Siahay, Margie Civitaria; Apalem, Delvia Rimesye; Peilouw, Marios (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
A department is part of an organ of higher education, so a department building tends to have a significant level of activity. The academic community consisting of students, educators, and employees carry out activities dynamically so that spaces are needed that are able to answer current needs. Space is seen as a reflection of human activity. Spaces that have the right function will be able to improve the quality of space. On the other hand, there are standards that can be used to identify how much space units and what space needs are priority spaces in a lecture building, so it is deemed necessary to re-identify space requirements. This research uses a mixed method, or mixed method where researchers explore qualitatively and quantitatively in one study simultaneously based on the standards used. The results of this study show that the spaces needed by a department in Ambon State Polytechnic include theoretical lecture rooms, department head workspaces, and lecturer workspaces. While other needs are still considered as shared facilities. This shows that a department building at Ambon State Polytechnic requires space that can accommodate the activities of the academic community comprehensively. Keywords: Spaces, Spatial, Spatial Needs